Peroxisome Proliferator-Activated Receptor Alpha Mediates the Beneficial Effects of Atorvastatin in Experimental Colitis - Basso, Paulo José; Sales-Campos, Helioswilton; Nardini, Viviani; Duarte-Silva, Murillo; Alves, Vanessa Beatriz Freitas; Bonfá, Giuliano; Rodrigues, Cassiano Costa; Ghirotto, Bruno; Chica, Javier Emílio Lazo; Nomizo, Auro; Cardoso, Cristina Ribeiro de Barros (Frontiers in Immunology, 2021)
The current therapeutic options for Inflammatory Bowel Diseases (IBD) are limited. Even using common anti-inflammatory, immunosuppressive or biological therapies, many patients become unresponsive to the treatments, immunosuppressed or unable to restrain secondary infections. Statins are cholesterol-lowering drugs with non-canonical anti-inflammatory properties, whose underlying mechanisms of action still remain poorly understood. Here, we described that in vitro atorvastatin (ATO) treatment was not toxic to splenocytes, constrained cell proliferation and modulated IL-6 and IL-10 production in a dose-dependent manner. Mice exposed to dextran sulfate sodium (DSS) for colitis induction and treated with ATO shifted their immune response from Th17 towards Th2, improved the clinical and histological aspects of intestinal inflammation and reduced the number of circulating leukocytes. Both experimental and in silico analyses revealed that PPAR- expression is reduced in experimental colitis, which was reversed by ATO treatment. While IBD patients also downregulate PPAR- expression, the responsiveness to biological therapy relied on the restoration of PPAR- levels. Indeed, the in vitro and in vivo effects induced by ATO treatment were abrogated in Ppara-/- mice or leukocytes. In conclusion, the beneficial effects of ATO in colitis are dependent on PPAR-, which could also be a potential predictive biomarker of therapy responsiveness in IBD.